PERSAINGAN USAHA TIDAK SEHAT DALAM PENENTUAN HARGA KARGO PESAWAT TERBANG DI INDONESIA - Alfatri Anom dan Yeni Santi (Normative Jurnal Ilmiah Hukum, 2020)
The rapid growth of e-commerce transactions in Indonesia triggers the increase of airplane cargo service demands. From the information provided by the KPPU, several airplane cargo providers are suspected to conducting practices conflicting the UU No. 5 / 1999. The issues discussed in this paper are the analysis of unfair competitions in deciding cargo service price in Indonesia and the measurements KPPU take in performing law enforcement regarding this matter. This research is carried out by using normative juridical approach, the data are collected from secondary resources, the collected data are then processed with editing methods and are analyzed qualitatively. The forms of unfair competition conducted by airplane cargo providers in Indonesia are cartel and oligopoly. In tracing the unfair competition allegation, KPPU have performed investigations and summoned a number of parties involved in the practice. The practice of unfair competition in deciding airplane cargo service price brings disadvantages to customers and other business doers in the same field